High-performance liquid chromatography determination of praziquantel in tablets and raw materials - Mainardes, Rubiana M. [UNESP]; Cinto, Priscila O. [UNESP]; Gremião, Maria P.D. [UNESP] (My University, 2006)
A specific and sensitive high-performance liquid chromatographic method was developed for the assay of praziquantel in raw materials and tablets. It was also found that the excipients in the commercial tablet preparation did not interfere with the assay in the wavelenght selected. The method validation yielded good results and included the range, linearity, precision, accuracy, specificity and recovery.
Keywords: HPLC; Praziquantel; Quality control; praziquantel; accuracy; drug formulation; drug structure; high performance liquid chromatography; tablet formulation; validation process